Rodinný dům s kavárnou - Kabelková, Aneta (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Předmětem bakalářské práce je řešení a návrh novostavby rodinného domu s kavárnou. Novostavba se nachází v katastrálním území města Třebíč. Objekt je navržen jako samostatně stojící budova na pozemku v klidné lokalitě města Třebíč. Cílem práce bylo navržení objektu, který propojuje funkce bydlení pro 4–5 členů rodiny s kavárnou. Rodinný dům je navržen tak, aby poskytoval pohodlné a moderní zázemí pro rodinu, s důrazem na prostornost a komfort. Kavárna je navržena tak, aby byla otevřená pro veřejnost, přičemž zároveň nenarušovala soukromí obyvatel domu. Kavárna je koncipována s kapacitou cca 17 osob. Základová konstrukce je navržena ze železobetonových pasů. Obvodová stěna v suterénu je navržena z tvárnic ztraceného bednění a keramických tvárnic. Obvodové zdivo v nadzemní části a vnitřní nosné zdivo je řešeno z keramických tvárnic. Stropní konstrukce jsou navrženy jako železobetonová monolitická deska. Střešní konstrukce je řešena jako jednoplášťová plochá vegetační střecha. Celý dům je zateplen vnějším zateplovacím systémem (ETICS).

The subject of the bachelor thesis is the design and solution of a new family house with a café. The building is located in the cadastral area of Třebíč and is designed as a detached house situated on a plot in a quiet part of the town. The aim of the project was to create a design that combines residential accommodation for a family of 4–5 members with a small public café. The house is intended to provide comfortable and modern living conditions, with an emphasis on spaciousness and convenience. The café is designed to be accessible to the public, while ensuring that the privacy of the residents is not compromised. It has a seating capacity of approximately 17 people. The foundation is designed using reinforced concrete strip footings. The basement perimeter walls are constructed using permanent formwork blocks and ceramic blocks. The above-ground perimeter and internal load-bearing walls are made of ceramic blocks. The floor structure consists of monolithic reinforced concrete slabs. The roof is a single-skin flat green (vegetated) roof. The entire building is insulated using an external thermal insulation composite system (ETICS).
Family House with a Cafe
Keywords: Rodinný dům; kavárna; částečně podsklepený; základové pásy; zděná konstrukce; plochá střecha; vegetační střecha; monolitická stropní deska; ETICS.; Detached house; café; partial basement; strip foundation; brick construction; flat roof; green roof; monolithic ceiling slab; ETICS.